Co(II), Ni(II), Cu(II) and Zn(II) Metal Complexes of Hydrazone Schiff Base Ligand: Synthesis, Characterization, Thermal Behaviour, Antioxidant and Antimicrobial Studies - Umasare, Tushar S.; Patil, Sanjay K.; Pargaonkar, Jyotsna G. (Asian Journal of Chemistry, 2024)
The metal(II) complexes of ML type of Co(II), Ni(II), Cu(II) and Zn(II) were synthesized using hydrazone Schiff base, N',N"-((1E,2E)-acenaphthylene-1,2-diylidene)bis(2-hydroxy benzohydrazide), which was synthesized by the condensation of acenaphthaquinone and 2-hydroxy benzohydrazide (1:2 molar ratio) in ethanol and characterized by various spectroscopic and analytical techniques, including UV-visible, FTIR, 1H NMR, 13C NMR, LC-MS, TGA-DSC, powder XRD and atomic absorption measurements. The magnetic susceptibility and electronic spectral data suggested that the Ni(II) and Cu(II) complexes have octahedral geometry, while the Co(II) and Zn(II) complexes have tetrahedral geometry. It has also been found that all the metal(II) complexes are paramagnetic, except Zn(II) complex. The molar conductance values indicated that all the metal(II) complexes are non-electrolytes in DMSO solvent. The stability of metal(II) complexes, the absence of coordinated and lattice water molecules in complexes and the proposed formula were all validated by the thermal analysis. All the compounds have average crystallite sizes on the nanoscale, according to powder XRD results. All of the compounds were tested for their in vitro antimicrobial activities against six bacteria (B. subtilis, S. aureus, Corynebacterium, P. aeruginosa, K. pneumoniae and E. coli) and three fungi (C. albicans, A. flavus and A. niger) at two different concentrations.